2005
DOI: 10.1098/rspa.2004.1369
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulation of coherent effects in multiple scattering

Abstract: Using a combination of the stochastic Monte Carlo technique and the iteration procedure of the solution to the Bethe–Salpeter equation, it has been shown that the simulation of the optical path of a photon packet undergoing an n th scattering event directly corresponds to the n th–order ladder diagram contribution. In this paper, the Monte Carlo technique is generalized for the simulation of the coherent back–scattering and temporal correlation function of optica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…Alternatively, other recently developed methods that keep track of the phase of the propagating light can also be used to simulate enhanced backscattering. 29,30 In this paper, we model LEBS through Eq. (1) because a number of experimentally obtained results are in good agreement with the approach.…”
Section: Monte Carlo Methods For Simulation Of Lebsmentioning
confidence: 99%
“…Alternatively, other recently developed methods that keep track of the phase of the propagating light can also be used to simulate enhanced backscattering. 29,30 In this paper, we model LEBS through Eq. (1) because a number of experimentally obtained results are in good agreement with the approach.…”
Section: Monte Carlo Methods For Simulation Of Lebsmentioning
confidence: 99%
“…1 An opportunity to imitate directly the influence of varieties of structural and physiologic properties of biological tissues on the photon migration for a particular source-detector configuration makes MC a primary tool in biomedical optics and optical engineering. A number of MC codes have been developed in the past [1][2][3][4][5] and applied extensively for various biomedical applications, including light dosimetry modelling for photodynamic therapy treatment planning, 6 simulation of reflectance spectra of human skin, 7 analysis of fluorescence excitation in skin tissues, 8 imitation of photon migration in the brain, 9 two-dimensional images of skin by optical coherence tomography (OCT), 10 and others. It has been demonstrated that MC technique is able to provide a broad variety of practical solutions in a range of biomedical studies from single cells to the biopsy of specific biological tissues and whole organs.…”
mentioning
confidence: 99%
“…These effects are significant, and thus, require special consideration. Note also that with these simplifications, the simulation of the elastic field transfer turns to be exactly the same as simulations of light radiation in a random medium in the scalar field approach framework ( [25]). Additionally, to make the boundary conditions as distinct as possible from that of light scattering, we presently add a term accounting for the contribution of reflected radiation for every scattering event.…”
Section: Multiple Scattering In a Half-spacementioning
confidence: 94%
“…In earlier simulations of multiple light scattering, we developed the semi-analytic Monte-Carlo approach ( [25]) for a scalar model based upon the Bethe-Salpeter equation, successively describing a number of correlation and coherent phenomena in random media optics. Here, we generalize this approach for the multiple scattering of elastic waves, also in the scalar one-mode approximation.…”
Section: Introductionmentioning
confidence: 99%